Contests with size effects - Wolfgang Eggert; Martin Kolmar (Center for Economic Studies and ifo Institute (CESifo), 2004)
In this paper we analyze the structure of contest equilibria with a variable number of individuals. First we analyze a situation where the total prize depends on the number of agents and where every single agent faces opportunity costs of investing in the contest. Second we analyze a situation where the agents face a trade-off between productive and appropriative investments. Here, the number of agents may also influence the productivity of productive investments. It turns out that both types of contests may lead to opposing results concerning the optimal number of individuals depending on the strength of size effects. Whereas in the former case individual utility is u-shaped when the number of agents increases, the opposite holds true for the latter case. We discuss the implications of our findings for the case of anarchic societies and competition on markets.
Keywords: L10; D74; 330; size effects; contests; anarchy; competition; Wettbewerbstheorie; Marktstruktur